Bioenergetic Implications of the AMPKg3 R225W Mutation in Human Muscle - Hadzimustafic, Nina (Université d'Ottawa / University of Ottawa, 2020)
AMPK is a master regulator of cellular energy homeostasis. The gain-of-function AMPKg3 R225W mutation in human skeletal muscle increases resistance to fatigue during exercise, mitochondrial content, and glycogen storage. We demonstrate that primary myotubes exhibit increased OCR, decreased ECAR, increased FAO, and increased activities of several mitochondrial complexes. To examine whether functional effects are attributable to mitochondrial content, we inhibited AMPK; differences between R225W and control were diminished. Glycogen phosphorylase inhibition demonstrated normal respiration independent of glycogen. We examined markers of quality/quantity control of mitochondria. In R225W muscle, fusion markers increased, biogenesis markers remained unchanged, mTOR pathway was inhibited, and there was greater capacity for autophagic flux and mitophagy. We thus determine that bioenergetic effects of R225W are in part due to active AMPK, but also due to capacity for more robust mitochondria. Overall, R225W provides a model for evaluating effects of AMPK, and new avenues toward treatment of metabolic disease.
Keywords: metabolic flexibility; AMPK R225W mutation; mitochondrial dynamics; bioenergetic capacity